2020
DOI: 10.1007/s40656-020-00337-8
|View full text |Cite
|
Sign up to set email alerts
|

The history and philosophy of taxonomy as an information science

Abstract: We undeniably live in an information age-as, indeed, did those who lived before us. After all, as the cultural historian Robert Darnton pointed out: 'every age was an age of information, each in its own way' (Darnton 2000: 1). Darnton was referring to the news media, but his insight surely also applies to the sciences. The practices of acquiring, storing, labeling, organizing, retrieving, mobilizing, and integrating data about the natural world has always been an enabling aspect of scientific work. Natural his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
(10 reference statements)
0
6
0
Order By: Relevance
“…This ontological problem limits possibilities for racial justice because, inherently, the perceptions and behaviors of those individuals responsible for creating the environment (effectively a reverse or cyclical causal path) are either amorphous or completely unspecified in today's predominant conceptual frameworks for campus environment (Ledesma, 2016). The climate heuristic obfuscates how human beings coconstruct and experience the world through their racialized bodies in situated, temporal, and place-bound personal interactions (Kendig, 2011;Sundstrom, 2003;Tuck & McKenzie, 2015) and therefore reinforces, rather than challenges, whatever conditions might exist in a person's environment. At best, such ontological limitations invite observations of, say, white supremacy, rather than interrogations of how white supremacy operates, and at worst, they obscure the nature of white supremacy while perpetuating the epistemic erasure of the very bodies from whom data were collected.…”
Section: Indirect and Self-referential Indicators Of Climatementioning
confidence: 99%
“…This ontological problem limits possibilities for racial justice because, inherently, the perceptions and behaviors of those individuals responsible for creating the environment (effectively a reverse or cyclical causal path) are either amorphous or completely unspecified in today's predominant conceptual frameworks for campus environment (Ledesma, 2016). The climate heuristic obfuscates how human beings coconstruct and experience the world through their racialized bodies in situated, temporal, and place-bound personal interactions (Kendig, 2011;Sundstrom, 2003;Tuck & McKenzie, 2015) and therefore reinforces, rather than challenges, whatever conditions might exist in a person's environment. At best, such ontological limitations invite observations of, say, white supremacy, rather than interrogations of how white supremacy operates, and at worst, they obscure the nature of white supremacy while perpetuating the epistemic erasure of the very bodies from whom data were collected.…”
Section: Indirect and Self-referential Indicators Of Climatementioning
confidence: 99%
“…There has been, and continues to be, much debate between scientists and philosophers as to which approach is most efficacious, and this has resulted in the promulgation of several well-respected theories and schools of taxonomy. Textbooks on this subject could fill an entire section of the library (for example, see Mayr, 1969 ; Ereshefsky, 2000 ; Kendig and Witteveen, 2020 ).…”
Section: Applying Principles Of Taxonomy To the Field Of Contemplativ...mentioning
confidence: 99%
“…Our initial review of the Philosophy of Taxonomy literature ( Lubischew, 1969 ; Mayr, 1969 ; Ereshefsky, 2000 ) provided the theoretical and operational principles that informed our 2013 taxonomic approach. Further review for this iteration ( Walsh, 2006 ; Ereshefsky, 2007 ; Austin, 2017 ; Kendig and Witteveen, 2020 ) indicated that it would be beneficial to have a criterion-based set of standards for constructing meditation classification proposals. The following Four Criteria Model was developed to facilitate a standardized and compartmentalized explanandum for our new Three Tier Classification System presented in this paper; and as a potentially useful method for evaluating the relative efficacy of various other classification proposals.…”
Section: The Four Criteria: Guidelines For Constructing and Evaluatin...mentioning
confidence: 99%
“…Better analogies are available for taxonomy, free from the tensions caused when it is forced into a hypotheticodeductive straitjacket with an over-emphasis on apparent objectivity. One is taxonomy as an information science (see Kendig & Witteveen, 2020, and references cited therein). Another is taxonomy as map-making (see also Kitcher, 1984Kitcher, , 2001O'Hara, 1993).…”
Section: Taxonomy As 'Map-making'mentioning
confidence: 99%